Admission to hospital following head injury in England: Incidence and socio-economic associations - Tennant Alan (BMC, 2005)
Abstract Background Head injury in England is common. Evidence suggests that socio-economic factors may cause variation in incidence, and this variation may affect planning for services to meet the needs of those who have sustained a head injury. Methods Socio-economic data were obtained from the UK Office for National Statistics and merged with Hospital Episodes Statistics obtained from the Department of Health. All patients admitted for head injury with ICD-10 codes S00.0-S09.9 during 2001-2 and 2002-3 were included and collated at the level of the extant Health Authorities (HA) for 2002, and Primary Care Trust (PCT) for 2003. Incidence was determined, and cluster analysis and multiple regression analysis were used to look at patterns and associations. Results 112,718 patients were admitted during 2001-2 giving a hospitalised incidence rate for England of 229 per 100,000. This rate varied across the English HA's ranging from 91-419 per 100,000. The rate remained unchanged for 2002-3 with a similar magnitude of variation across PCT's. Three clusters of HA's were identified from the 2001-2 data; those typical of London, those of the Shire counties, and those of Other Urban authorities. Socio-economic factors were found to account for a high proportion of the variance in incidence for 2001-2. The same pattern emerged for 2002-3 at the PCT level. The use of public transport for travel to work is associated with a decreased incidence and lifestyle indicators, such as the numbers of young unemployed, increase the incidence. Conclusion Head injury incidence in England varies by a factor of 4.6 across HA's and PCT's. Planning head injury related services at the local level thus needs to be based on local incidence figures rather than regional or national estimates. Socio-economic factors are shown to be associated with admission, including travel to work patterns and lifestyle indicators, which suggests that incidence is amenable to policy initiatives at the macro level as well as preventive programmes targeted at key groups.